2015
DOI: 10.1007/978-3-319-24586-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Case-Based Policy and Goal Recognition

Abstract: We present the Policy and Goal Recognizer (PaGR), a casebased system for multiagent keyhole recognition. PaGR is a knowledge recognition component within a decision-making agent that controls simulated unmanned air vehicles in Beyond Visual Range combat. PaGR stores in a case the goal, observations, and policy of a hostile aircraft, and uses cases to recognize the policies and goals of newly-observed hostile aircraft. In our empirical study of PaGR's performance, we report evidence that knowledge of an adversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The TBM's agent interpreter recognizes the behaviors of hostile aircraft using its models of them (M A ). We showed that a case-based reasoning technique (Borck et al 2015), which uses features that model an agent's prior behaviors, performs well on this task. We later extended it with an active planner that "teases out" a hostile's behavior (to disambiguate it from others) and showed that this active planner further improves performance (Alford et al 2015).…”
Section: Oceanserveriver2mentioning
confidence: 98%
“…The TBM's agent interpreter recognizes the behaviors of hostile aircraft using its models of them (M A ). We showed that a case-based reasoning technique (Borck et al 2015), which uses features that model an agent's prior behaviors, performs well on this task. We later extended it with an active planner that "teases out" a hostile's behavior (to disambiguate it from others) and showed that this active planner further improves performance (Alford et al 2015).…”
Section: Oceanserveriver2mentioning
confidence: 98%
“…Behaviour recognition in beyond visual range (BVR) air combat has also been much researched. Borck et al (2015b) used case based behaviour recognition. The set of actions the agent attempts to recognize are: pursuit, whereby an agent flies directly at another agent, drag, whereby an agent tries to kinematically avoid a missile by flying away from it, and crank, whereby an agent flies at the maximum offset but tries to keep its target in radar.…”
Section: Related Workmentioning
confidence: 99%
“…In the past, researchers have mostly focused on the problem of target activity identification in air situation understanding [19]- [22]. Undoubtedly, activity recognition is of great help in enriching intention recognition knowledge.…”
Section: Introductionmentioning
confidence: 99%